2014
DOI: 10.1155/2014/816545
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Traditional Chinese Medicine Shuxuetong Injection on Random Skin Flap Survival in Rats

Abstract: Background. A Shuxuetong injection is traditionally used in Chinese medicine to treat “blood stasis and stagnation” (yu xue yu zhi). We investigated the effect of such injection on the survival of random skin flaps. Methods. McFarlane flaps were established in 60 rats divided into two groups. Postoperative celiac injections were given to both groups for 7 days. Shuxuetong was injected into the test group, and saline was injected into controls. On day 7, tissues were stained with H&E (hematoxylin-eosin) stain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…To quantify the survival area, flaps were photographed and measured by graph paper. Results were expressed as proportions of viable area by the weight of the graph paper, calculated using the following formula 7 :…”
Section: Flap Survival Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…To quantify the survival area, flaps were photographed and measured by graph paper. Results were expressed as proportions of viable area by the weight of the graph paper, calculated using the following formula 7 :…”
Section: Flap Survival Measurementmentioning
confidence: 99%
“…To date, several pharmacological agents have been investigated for their effectiveness in preventing or reversing ischemia in skin flaps, such as vinpocetine, 4 polydeoxyribonucleotide, 5 and vascular endothelial growth factor (VEGF), 6 in addition to the traditional Chinese medicine Shuxuetong. 7 Huangqi has been used for thousands of years in China and East Asia. 8 Huangqi injection 9 involves preparation of an extract of Radix astragali: the major component is astragalosides, but other pharmacological ingredients include polysaccharides, flavones, and amino acids.…”
mentioning
confidence: 99%
“…In addition, certain studies have confirmed that VEGF promotes revascularization (17,18), thus enhancing the survival of skin flaps. Numerous studies have focused on herbal remedies to improve the survival of skin flap by inhibiting ischemia-reperfusion injury, reducing inflammatory reaction and accelerating angiogenesis, with specific examples including Xuebijing, Shuxuetong and Huangqi (3,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Local random-pattern skin flaps are segments of skin taken from a donor area and commonly used in plastic surgery for reconstruction after trauma and surgical procedures [1,2]. Nevertheless, the current challenge is distal necrosis, increasing the cost of treatment and hospitalization.…”
Section: Introductionmentioning
confidence: 99%